2017
DOI: 10.1111/jfpp.13336
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chitosan coating incorporated with ethanolic extract of propolis on the quality of refrigerated chicken fillet

Abstract: Chitosan is considered as a functional packaging component for maintaining the quality and increasing the shelf life of perishable foods include meat, poultry, fish, dairy products, and all cooked leftovers. The present study was conducted to evaluate edible coating of chitosan (2%) containing ethanolic extract of propolis (1% and 2%) on microbiological (mesophilic aerobic, psychrotrophic, lactic acid bacteria, coliforms, and Staphylococcus aureus counts), chemical (TBARS, TVN and Peroxide values) and sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 41 publications
(64 reference statements)
11
32
0
Order By: Relevance
“…However, TBARS values were comparable to control till the storage period studied. Similar observations were reported by Hassanzadeh et al () and Jonaidi Jafari, Kargozari, Ranjbar, Rostami, and Hamedi (), where the TBARS value increases due to storage but presence of chitosan did not alter the lipid peroxidation levels when used alone or in combination with pomegranate juice or propolis extract.…”
Section: Resultssupporting
confidence: 89%
“…However, TBARS values were comparable to control till the storage period studied. Similar observations were reported by Hassanzadeh et al () and Jonaidi Jafari, Kargozari, Ranjbar, Rostami, and Hamedi (), where the TBARS value increases due to storage but presence of chitosan did not alter the lipid peroxidation levels when used alone or in combination with pomegranate juice or propolis extract.…”
Section: Resultssupporting
confidence: 89%
“…Gutiérrez‐Cortés and Suarez Mahecha () reported that the TVB‐N value of sausages treated with 0.8 mg/ml ethanol propolis extract was lower than that of the control group (treated with 96% alcohol) and of the other treatment group (treated with 0.2 g/kg sodium nitrite and sodium erythorbate). Jonaidi Jafari, Kargozari, Ranjbar, Rostami, and Hamedi () showed that coating of chicken fillets with ethanolic extract of propolis in combination with chitosan solution could delay the increase in TVBN content. According to Nessianpour et al (), the TVBN value of S. tumbil fillets for control group was higher than the others, and the lowest value was observed (38.33 mg N/100 g) in the S. tumbil fillets coated with gelatin–PE at the end of the storage.…”
Section: Resultsmentioning
confidence: 99%
“…These abilities can be improved by additives such as antioxidants derived from natural sources [10,11]. Edible chitosan films provide some characteristics that help to preserve the freshness of meat [12][13][14]; moreover, these types of films present some antimicrobial activity against pathogens and spoilage bacteria in foods and act as antioxidant agents [15,16].…”
Section: Of 16mentioning
confidence: 99%